Role of basophils in protective immunity to parasitic infections - Eberle, Jörg; Vöhringer, David (Seminars in Immunopathology, 2016)
Basophils have been recognized as important players for protective immunity against a variety of different endo- and ectoparasites. Although basophils represent a relatively rare and short-lived cell type, they produce large quantities of effector molecules including histamine, cytokines, chemokines, and lipid mediators which promote type 2 immune responses. Basophils can be activated either directly by parasite-derived factors or indirectly by recognition of parasite-derived antigens via IgE bound to its high-affinity receptor Fc?RI on the cell surface. Many parasitic infections cause expansion and tissue recruitment of basophils, but the role of basophils for protective immunity remains poorly understood. The development of basophil-deficient mouse models over the past few years makes it possible to study their contributions in various infections. We review here the current knowledge regarding the role of basophils for protective or immunomodulatory functions of basophils mainly during infections of mice with protozoan parasites, helminths, and ectoparasites.
EVALuna2:25880